Cloning, recombinant production, crystallization and preliminary X-ray diffraction analysis of SDF2-like protein from Arabidopsis thaliana - Radzimanowski, Jens; Ravaud, Stéphanie; Schott, Andrea; Strahl, Sabine; Sinning, Irmgard (Acta crystallographica. Section F, Structural biology communications, 2010)
The stromal-cell-derived factor 2-like protein of Arabidopsis thaliana (AtSDL) has been shown to be highly up-regulated in response to unfolded protein response (UPR) inducing reagents, suggesting that it plays a crucial role in the plant UPR pathway. AtSDL has been cloned, overexpressed, purified and crystallized using the vapour-diffusion method. Two crystal forms have been obtained under very similar conditions. The needle-shaped crystals did not diffract X-rays, while the other form diffracted to 1.95 Å resolution using a synchrotron-radiation source and belonged to the hexagonal space group P61, with unit-cell parameters a = b = 96.1, c = 69.3 Å.